Inovasi Pembelajaran Berbasis Kearifan Lokal Melalui Batik Ecoprint di TK Dharma Wanita Macanan 2: Inovasi Pembelajaran Berbasis Kearifan Lokal Melalui Batik Ecoprint di TK Dharma Wanita Macanan 2 - Nururrohmah, Taufika; Rahmawati, Dwi Amalia; Safitri, Dewi (Early Stage, 2025)
This study explores the innovation of local wisdom-based learning through Batik Ecoprint at TK Dharma Wanita Macanan 2. The purpose of the research is to investigate how Batik Ecoprint, utilizing natural materials such as leaves and flowers, can be integrated into early childhood education to promote creativity, environmental awareness, and the preservation of cultural heritage. The research employs a qualitative approach with a case study design, involving participatory observation, interviews, and documentation analysis to collect data on the implementation of this learning method. The main findings indicate that Batik Ecoprint enhances children's fine motor skills, stimulates creativity, and strengthens their cultural identity while fostering environmental consciousness. This innovation proves to be an effective and engaging way to teach children about the significance of local culture and environmental preservation. The study suggests that learning methods based on local wisdom can provide holistic educational experiences that are both meaningful and relevant to young learners